A study on the perceptions of librarians and staff on the impact of technology on the organization and personnel of selected academic libraries in CALABARZON - Torres, Efren M., Jr (Institute of Library and Information Science, University of the Philippines Diliman, 2002)
New technologies are now a part of everyday life, with the majority of daily activities revolving around the use of computers. Truly, information professionals and workers have been impacted by the rapid changes in technology in years. A review of the literature revealed little research studies that have been conducted to investigate the impact of technology on the organization and personnel level locally. Therefore, the purpose of this study was to find out how the librarians and staff from selected academic libraries in CALABARZON perceive the impacts of technology in their workplace.